Financial accounting, reporting & analysis - Maynard, Jennifer (Lecturer on financial accounting) (Oxford University Press, 2017)
Covering all the accounting issues and reporting standards (IAS, IFRS) that an accounting student needs to know, this text provides a fresh, decision-usefulness approach that will enhance students' interpretative skills and take their understanding to the next level.